Development of Clinical Training Models for Comprehensive Emergency Obstetrics and Neonatal Care (Ceonc/Ponek) and Facilitative Supervision for Improving Hospital Performance - Hadijono, Soerjo; Samsudi, Samsudi; Florentinus, Totok Sumaryanto; Noorpramono, Noorpramono (Universitas Negeri Semarang, 2019)
Training investments and provision of facilities can only mobilize a part of healthcare production machines, and will be successfully drive it if they are fully supported by the local institutions / government and clinical training quality assurance system. In medical education and clinical training, the behaviours and attitudes modeled by professional practitioners are a special mechanisms in which participants will implicitly